Problem-Based Learning Model (PBL) by Utilizing Videos on The Competency of UKEL Bend Buns on Learning Outcomes of Class XI SMKN 6 Surabaya - Arifatul Hasanah; Sri Usodoningtyas; Biyan Yesi Wilujeng; Mutimmatul Faidah (Adornata : Ethnobeauty and Wellness Journal, 2025)
Abstract The Problem Based Learning (PBL) model that utilizes video media is an innovative approach to skill learning, especially in the competence of the ukel bend bun. This approach is expected to be able to improve the understanding and skills of students who have been experiencing difficulties mastering the material optimally. This study aims to examine the characteristics of learning video media, analyze the implementation of the syntax of the PBL learning model, determine the improvement of student learning outcomes, and evaluate student motivation towards the use of learning videos in the PBL model on the competence of the bending bun. The type of research uses a quantitative approach with a One-Group Pretest-Posttest design without a control group. The research sample was 31 students in grade XI TKC 2 SMKN 6 Surabaya. The data collection methods used were observation, questionnaires, and cognitive learning outcome tests. The results showed that the characteristics of video media were very feasible to use with an average validation of 90%, the implementation of PBL syntax was carried out very well with an average of 100%, there was a significant increase in learning outcomes from an average of pretest 83.06 to a posttest of 95.96 (p < 0.05), and student learning motivation was relatively high with an average score of 87.57%. This study proves that the application of a problem-based learning model by utilizing video media is effective in increasing student learning outcomes and motivation in the competence of the ukel bend bun at SMKN 6 Surabaya.Keywords : Problem-Based Learning, Video Media, Learning Outcomes, Ukel Bend Bun.